Pengaruh Pergantian CEO dan Pengungkapan CSR sebagai Maslahat Mursalah terhadap Manajemen Laba dengan Struktur Corporate Governance sebagai Variabel Moderasi - Adhelia Desi Prawestri; Bambang Setyobudi Iriyanto; Negina Kencono Putri (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine whether CEO turnover and CSR disclosure as maslahat mursalah are moderated by corporate governance structure consisting of independent commissioners, audit committee and institutional ownership partially affect earnings management. This study uses secondary data from manufacturing companies during 2019. Sampling technique using purposive sampling. The data were collected and analyzed using moderated regression analysis (MRA). The result indicate that CEO turnover and CSR disclosure as maslahat mursalah have no effect on earnings management. Independent commissioners and institutional ownership does not moderate the effect of CEO turnover on earnings management. The audit committee weakens the positive influence of CEO turnover on earnings management. The audit committee and institutional ownership do not moderate the effect of CSR disclosure as masalaht mursalah on earnings management. This study has limitations on audit committee measurement indicators that are less able to reflect the actual performance of audit committees, so that future research is expected to use more appropriate indicators.